ITTO project PD 12/97 Rev.1 (F) - Forest, science and sustainability: the Bulungan model forest: completion report phase I 1997-2001 - Center for International Forestry Research (CIFOR and ITTO, 2002)
This document is a report on the implementation of an initial project of Bulungan Research Forest in East Kalimantan, Indonesia 1997-2001 with financial support from International Tropical Timber Organization (ITTO). It contains an executive summary, the main text of the project objectives and outputs, brief report on technical and scientific aspects, lessons learned and recommendations for future projects. The general objective of the present research is to carry out systematic investigation of how to achieve long-term forest sustainability for a 'large forest landscape' by integrating social, ecological and silvicultural aspects. The first phase focussed on gathering baseline information on the physical and human environment. Specific two objectives are: (1) assessment of the effect of Reduced-Impact Logging (RIL) on biodiversity, conservation, ecology and socio-economics; (2) assesment of rural development trends and future policy options including the effects of macro-level development activities on people dependent on the forest.